1956
DOI: 10.1071/ar9560482
|View full text |Cite
|
Sign up to set email alerts
|

Sweat glands in Zebu (Bos indicus L.) and European (B. taurus L.) cattle. I. Size of individual glands, the denseness of their population, and their depth below the skin surface

Abstract: Number of sweat glands per unit area of skin, their size, and their depth below the epidermis were compared in skin biopsy specimens obtained from the midside region of two Zebu and three European breeds of dairy cattle. Within Zebu breeds, comparisons were made between sweat glands from the midside and the dewlap. Zebus were found to have much larger and more numerous sweat glands than European animals. Within Zebus, sweat glands were slightly larger, and much more numerous, on the midside than on the dewlap.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
2

Year Published

1968
1968
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 1 publication
3
34
1
2
Order By: Relevance
“…On the basis of these data each gland in the ox, therefore, can be considered to secrete at a mean rate of 0 0166d1./hr compared with 0 013 #1./hr in the goat. The volume of a sweat gland in the goat has been found here to be approximately 0-003 mm3 whereas that in cattle (B. taurus) was found by Nay & Hayman (1956) to be 0f01 mm3. Thus it can be inferred that in relation to sweat gland volume the output from the sweat glands of the goat during their period of activity is at least comparable with that from cattle sweat glands.…”
Section: Discussioncontrasting
confidence: 46%
“…On the basis of these data each gland in the ox, therefore, can be considered to secrete at a mean rate of 0 0166d1./hr compared with 0 013 #1./hr in the goat. The volume of a sweat gland in the goat has been found here to be approximately 0-003 mm3 whereas that in cattle (B. taurus) was found by Nay & Hayman (1956) to be 0f01 mm3. Thus it can be inferred that in relation to sweat gland volume the output from the sweat glands of the goat during their period of activity is at least comparable with that from cattle sweat glands.…”
Section: Discussioncontrasting
confidence: 46%
“…The formol-saline samples were processed on lines similar to those described by Nay and Hayman (12) with slight modifications. The mounting medium used (Table 2).…”
Section: Materiais and Methodsmentioning
confidence: 99%
“…Bos indicus cattle, with their higher sweat gland density, tend to have higher sweating rate (Schleger and Turner 1965). The sweat glands of Bos indicus are baggy-shaped, higher in volume (Pan, 1963), and closer to the skin surface (Nay and Hayman 1956) than those of Bos taurus. Comparative studies found that Bos indicus are more dependent upon increased sweating to dissipate excess body heat based on higher sweating rates, lower rectal temperature and lower respiration rate, while Bos taurus are more likely to utilize an increase in respiration rates to dissipate heat based on higher respiration rate and higher rectal temperature (Koatdoke, 2008).…”
Section: Sweatingmentioning
confidence: 99%